2021
DOI: 10.15244/pjoes/123922
|View full text |Cite
|
Sign up to set email alerts
|

Do Seasonal Changes and Climate Effect the Prevalence of Antibiotic Resistance of <i>Acinetobacter calcoaceticus-baumannii</i> Complex?

Abstract: The high rate of carbapenem resistant Acinetobacter calcoaceticus-baumannii Complex (ABC) is indicated as a threat to public health. We aimed to determine the ABC isolated from Near East University hospital from 2016 to 2019 based on seasonality and climate changes. A total of 218 patients were examined between 2016 and 2019. All isolates were healthcare-acquired isolates, which are defined as those obtained after 48 hours of admission. All isolates were identified by a Phoenix 100 System. Antibiotic susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Climate and seasonal changes can affect the diagnosis of infections in humans and direct infection prevention struggles. Studies about this area have emphasized that gram-negative bacteria cause more frequent infections during the summer months (21). According to a study conducted by Chazan et al, it was shown that BSI caused by Escherichia coli increased significantly in the summer months (22).…”
Section: Discussionmentioning
confidence: 99%
“…Climate and seasonal changes can affect the diagnosis of infections in humans and direct infection prevention struggles. Studies about this area have emphasized that gram-negative bacteria cause more frequent infections during the summer months (21). According to a study conducted by Chazan et al, it was shown that BSI caused by Escherichia coli increased significantly in the summer months (22).…”
Section: Discussionmentioning
confidence: 99%